2011
DOI: 10.1108/02632771111178391
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for improving safety performance of repair, maintenance, minor alteration and addition (RMAA) works

Abstract: Purpose -Managing and maintaining infrastructure assets are one of the indispensible tasks for many government agencies to preserve the nations' economic viability and social welfare. To reduce the expenditures over the life-cycle of an infrastructure asset and extend the period for which the asset performs effectively, proper repair and maintenance are essential. While repair, maintenance, minor alteration and addition (RMAA) sector is expanding in many developed cities, occurrences of fatalities and injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The targeted respondents must fulfill some set of criteria before their invitations, and these include (a) the respondent must have a broad level of experience and leadership in the construction industry; (b) the respondent must have utilized BIM and implemented sustainability practices in previous or current projects; and (c) the respondent should be well acquainted with BIM and sustainability concepts as well as a robust understanding of their interrelationships.Moreover,Giel and Issa (2016) noted that a 2-3 round of Delphi survey is sufficient to attain the required consensus from the expert panel. Hence, this study adopted a two-round Delphi survey over a 5-month period involving 14 experts Hon, Chan, and Chan (2011). noted that a Delphi expert panel must consist of a minimum of seven respondents, andTuroff (1970) caps the size of an expert panel at 50 members.…”
mentioning
confidence: 99%
“…The targeted respondents must fulfill some set of criteria before their invitations, and these include (a) the respondent must have a broad level of experience and leadership in the construction industry; (b) the respondent must have utilized BIM and implemented sustainability practices in previous or current projects; and (c) the respondent should be well acquainted with BIM and sustainability concepts as well as a robust understanding of their interrelationships.Moreover,Giel and Issa (2016) noted that a 2-3 round of Delphi survey is sufficient to attain the required consensus from the expert panel. Hence, this study adopted a two-round Delphi survey over a 5-month period involving 14 experts Hon, Chan, and Chan (2011). noted that a Delphi expert panel must consist of a minimum of seven respondents, andTuroff (1970) caps the size of an expert panel at 50 members.…”
mentioning
confidence: 99%
“…Some may be over-confident with their experience and thus neglect the importance of safety compliance. Whatever the reason may be, it is suggested that the government or the Occupational Safety and Health Council should put more effort into uplifting the safety awareness and knowledge of RMAA practitioners at the subcontractors’ level [30]. …”
Section: Discussionmentioning
confidence: 99%
“…The semi-structured interview was conducted in order to obtain the answers to the pre-defined questions and to provide an opportunity for the specialists to express their experiences of health performance assessment if they wished. Semistructured interviewing has been used in various OHS research areas [22][23][24]. The specialists were selected through non-random purposive sampling (predetermined), and the individuals who were in the best position to provide the required information were selected.…”
Section: Stage1: Semi-structured Interviewmentioning
confidence: 99%